2020
DOI: 10.3389/fmed.2020.00451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Distribution and Prognostic Value of New Tumor-Infiltrating Lymphocytes in HCC Based on a scRNA-Seq Study With CIBERSORTx

Abstract: Hepatocellular carcinoma (HCC) is a commonly diagnosed cancer with high mortality rates. The immune response plays an important role in the progression of HCC. Immunotherapies are becoming an increasingly promising tool for treating cancers. Advancements in scRNA-seq (single-cell RNA sequencing) have allowed us to identify new subsets in the immune microenvironment of HCC. Yet, distribution of these new cell types and their potential prognostic value in bulk samples from large cohorts remained unclear. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Since the abundance and activity of TILs can affect the survival time of patients with various tumors [ 17 , 18 ], we evaluated the correlation of ALYREF with TILs by TIMER and TISIDB. In TIMER, ALYREF was found to be positively linked with the level of immune cell subset infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Since the abundance and activity of TILs can affect the survival time of patients with various tumors [ 17 , 18 ], we evaluated the correlation of ALYREF with TILs by TIMER and TISIDB. In TIMER, ALYREF was found to be positively linked with the level of immune cell subset infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, scRNA-seq is relatively expensive, so only a limited number of sample datasets were available. However, the information from scRNA-seq can be very meaningful for exploring the characteristics of each cell subpopulation from bulk samples and the interaction of each cell in the TIME [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that, when all kinds of immune cells in the TME reach a certain balance, they will spur immune activation, thus promoting the occurrence of immune escape [ 18 ]. Increasing evidence has shown that tumor-infiltrating immune cells (TICs) affect the biological behavior of HCC cells and ultimately affect the prognosis of patients [ 19 , 20 ]. In addition, the results of some latest clinical trials and medical studies showed that immunotherapy or combined with immunotherapy was more beneficial to patients with advanced HCC [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%